(untitled) (Integral Research, 2025)
The present research paper presents a sociological analysis of the mindset of highly educated women (postgraduates, professional degree holders, and Ph.D. scholars) in the selected blocks of Buxar district, Bihar, namely Buxar, Chausa, and Rajpur. The study examines their mental and psychological condition in the context of modern social transformation, including the expansion of education, media freedom, growing awareness of gender equality, and the persistence of traditional patriarchal norms. Based on a mixed-method approach involving surveys and semi-structured interviews, the study includes 200 highly educated women. The findings reveal that despite outward empowerment, most women internally experience “marginal consciousness” and “dialectical tension.” Family expectations, career balance, security-related concerns, and lack of social capital significantly affect their mental health and self-perception.